Penyaluran Lulusan Secara Langsung Semi Langsung Dan Tak Langsung - Wiwin Malindo (Jurnal Pendidikan Sepanjang Hayat, 2020)
This thesis research uses descriptive qualitative method, the researcher acts as a non-participatory research subject, data collection techniques used are interviews, observation and documentation study, data equivalence is carried out by triangulation techniques.This thesis research was conducted because LKP Lubuk Akal was the only LKP in Bengkulu City that had a graduate distribution program, the distribution program for graduates at the Lubuk Akal LKP was carried out in three ways namely, 1). Direct distribution of graduates is the distribution of graduates that are planned and conducted by the head of LKP without involving other pockets, 2.) semi-direct distribution, is channeling by involving the Depnakers / BLK as the party delivering the graduates. 3). indirect distribution is distribution that involves other parties, namely intermediaries, intermediaries are usually individuals who understand and master the distribution of graduates who are skilled in sewing. Distribution of graduates at LKP Lubuk Akal has been conducted since 2016 until now, the program and the implementation of graduate distribution are conducted because the LKP chairman has moral responsibilities and obligations and his conscience is called to try to channel graduates so that LKP graduates get jobs and income. Key words: responsibility to graduates